Politeness Strategies In Jane Eyre Movie (A Pragmatic Perspective) - Wulandari, Romadhani, Agus Wijayanto, Ph.D, Dr. Maryadi, M. A. (2017)
Politeness is one of the central concepts of pragmatics. It is the way how people save other people's face and feeling in communication. This research is a pragmatic study on politeness strategies employed by the main characters in Jane Eyre movie. The objectives of this research are (1) to describe the kinds of politeness maxims followed by the characters in Jane Eyre movie and (2) to explain the underlying reasons of the characters in Jane Eyre movie in using politeness strategy. This research used descriptive qualitative approach. The data were in the form of utterances which contain politeness strategies. The data source was Jane Eyre movie English manuscript. The data were collected by documentation technique, and the steps are watching, classifying, coding and analyzing. The results of the research show two important points. First, there are ten types of politeness strategies employed by the main characters in Jane Eyre movie: Tact Maxim (13 out of 113), Generosity Maxim (23), Approbation Maxim (25), Modesty Maxim (5), Agreement Maxim (6), Sympathy Maxim (11), Obligation Maxim(14 speaker to others and 2 others to speaker), Opinion Reticence Maxim(6) and feeling Reticence Maxim(8).Second, the underlying reasons of the characters in using politeness strategies are Commanding, Offering a help, Promising, Requesting, Praising, Expressing amazement, Giving reinforcement, Expressing Sympathy and Hopes, Apologizing, Thanking, Clarifying, Forgiving, Suggesting and Covering Suppressing Feeling. The selection of maxims which were followed to convey the reasons depended on the context situation background. Keywords: pragmatic, politeness strategy, Jane Eyre